THE RELATIONSHIP BETWEEN PARENTS THROUGH THE EVENTS OF TEMPER TANTRUMS IN CHILDREN'S PRE-SCHOOL (AGES 3 TO 6 YEARS OLD) AT PUSPA BANGSA KINDERGARTEN BOGOR: HUBUNGAN POLA ASUH ORANG TUA DENGAN KEJADIAN TEMPER TANTRUM PADA ANAK PRA SEKOLAH (USIA 3 SAMPAI 6 TAHUN) DI PAUD PUSPA BANGSA KOTA BOGOR - Noor Siti Noviani Indah Sari (Jurnal Ilmiah Wijaya, 2018)
Tantrum temperature is a burst of emotions that are explosive and uncontrolled and often appear in children aged 15 months to 6 years. Tantrums are characterized by crying, shouting and violent or aggressive body movements such as throwing things, rolling on the floor, banging your head and stamping your feet on the floor. The way parents take care of children plays a role in tantrums. Another study at Northwestern Feinberg in 2012, based on a survey of nearly 1500 parents, this study found that 84% of children aged 2-5 years vent their frustrations by raging in the past month and 8.6% of them have daily tantrums which is precisely if it happens every day is not normal. Whereas in Indonesia, toddlers who usually experience this within one year, 23-83% of children aged 2-4 years have experienced temper tantrums. The purpose of this study was to determine the relationship of parenting parents with the incidence of temper tantrums in preschool children (ages 3 to 6 years) in PAUD Puspa Bangsa Bogor City. This study uses a descriptive analysis research design. The population of this research is all parents who have pre school children (aged 3 to 6 years) located in PAUD Puspa Bangsa Bogor, with the sample are 60 respondents and the researcher using total sampling techniques. Then, the data collection are using interview techniques at the preliminary study stage and questionnaires at the research site. The data analysis using Chi Square. In conlcusion, the results of the study showed that parenting in the PAUD PuspaBangsa Bogor is positive parenting it is reached as 32 or 53% of parents while negative parenting as much as 28 or 47% of parents. And for the occurrence of temper tantrums, 27 or 45% of children experience temper tantrums and 33 or 55% of children do nottemper tantrums. The results showed there was no relationship between parenting style with the incidence of temper tantrums in preschool children (aged 3 to 6 years) in Puspa Bangsa PAUD Bogor, α (0.05) and p value of 0.446.